Design of Fuzzy Expert Systems and Its Applications in Some Medical Areas - Allahverdi, Novruz (International Journal of Applied Methods in Electronics and Computers, 2014)
This paper is the survey of studies that include design processes of some fuzzy expert systems for applications in some medical area. Recent studies of us that include fuzzy expert systems that make use of fuzzy logic method were described. Some of fuzzy expert systems mentioned in this paper have been developed as first time. Followings were investigated; the risk of prostate cancer, risk of coronary heart disease, degree of child anemia, determination the level of iron deficiency anemia, diagnosis of periodontal dental disease, determination of drug dose and etc. All designed fuzzy expert systems can help in support decision process of physicians. It can be claimed that in many cases such systems can help the physicians in diagnostics, treatment of illness, patient pursuit, prediction of disease risk and etc. As can be seen from the paper accuracies ratios of the proposed FESs were find as high by doctors involved to studies. Robustness and reliabilities of the developed FESs were proved on patients by doctors. The numbers and other arguments that support our claim can be found in the paper.